Plant knowledge richness in the Sundanese upland village: A case study in Sindangsari, West Java, Indonesia - Rini Soemarwoto; Johan Iskandar (Society for Indonesian Biodiversity, 2021)
Abstract. Soemarwoto R, Iskandar J. 2021. Plant knowledge richness in the Sundanese upland village: A case study in Sindangsari, West Java, Indonesia. Biodiversitas 22: 3722-3735. According to ecological history, Sundanese people of West Java, Indonesia, have highly rich knowledge of plants. However, due to population increase, rapid development of market economy, and rapid change of rural ecosystem, the local plants knowledge has tended to decrease rapidly. This research’s objective is to elucidate the plant knowledge richness of the Sundanese. The study was undertaken in the upland village of Sindangsari, West Java, using mixed-method with ethnobotanical approach, from July to August 2017, and March 2018. The study found 204 landraces which consisted of 181 species, representing 161 genera, and 70 families. The use of plants could be classified into food, spices, medicine, construction, ornament, cosmetic, commercial plants, fodder, industry, food color, erosion control, and social function. The highest secondary citations, that is plants for food and medicine, were known by less than 50% of respondents; other plants were hardly known, recognized only by 0.1% to 0.5% of respondents. The results showed little practical knowledge among the younger generation. The intensive mobility of young population between the village and the city induces intergenerational transfer of knowledge between old and young generations mainly through oral narratives. This study concludes that it is important to consider population mobility of the young generation to predict knowledge loss.